Strength training for Rugby Union: The general preparation phase - Corcoran, G.
The purpose of this paper is to address pre-season training in rugby union, with the focus on weight training in the general preparation phase. The issues addressed include the manipulation of several key variables including frequency, intensity, volume and periodisation in relation to the effectiveness of achieving specific training outcomes in the strength program. The goal is to optimise athletic performance while reducing risk of injury. The article addresses the conventional approach to periodisation to solve program goals sequentially, encompassing 3 mesocycles including hypertrophy, strength and power. The periodised plan is the most effective way to vary training stimulus and is an essential component of our training plan. Effective strength programs not only achieve physical performance benefits, but also contribute to reducing the risk of injury. The strength and conditioning coach needs to be aware of time constraints on their athletes and aim to ensure our programs are time efficient and practical whilst still achieving our program objectives.